INVESTIGATING THE INTERACTION BETWEEN FINANCIAL DEVELOPMENT AND CARBON DIOXIDE EMISSIONS IN AFRICA: A SPATIAL ECONOMETRIC ANALYSIS - Maldino Pramono; M. Abd. Nasir (Jurnal Ekonomi dan Bisnis Airlangga, 2026)
Introduction: Although Africa contributes only a small share of global carbon emissions, it experiences disproportionate economic and environmental losses from climate change. This study examines the relationship between financial development and carbon dioxide emissions in Africa by identifying spatial interdependence patterns and assessing both direct and spillover effects across countries. Methods: This study employs a quantitative approach using the Spatial Durbin Model (SDM). This study examines 46 African countries over a 15-year period (2009–2023). Results: The findings reveal significant spatial interdependence and clustering of carbon emissions across African countries, indicating strong cross-country spatial linkages in emission dynamics. Financial development has a positive and statistically significant direct effect on carbon emissions. However, the indirect spillover effects on neighboring countries are insignificant, suggesting limited regional financial integration in Africa. Conclusion and suggestion: Financial development increases carbon emissions directly but shows insignificant spillover effects. Therefore, emission reduction policies should focus on high emission clusters, while financial institutions and regional organizations should strengthen green finance and regional cooperation to support sustainable development in Africa.